The Effect of Infrastructure and Economic Growth on Poverty Reduction in Indonesia - Simanjuntak, Rio Saputra; Solihin, Achmad (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the impact of infrastructure development and economic growth on poverty reduction in Indonesia from 2014 to 2023. Utilizing panel data from 34 provinces, the analysis employs static regression 3 models CEM, FEM, and REM to evaluate the significance of education, health, telecommunications, electricity, road infrastructure, and regional GDP growth on poverty rates. The Hausman and Chow tests identified FEM as the optimal model, revealing that education infrastructure (school-to-population ratio), telecommunications (mobile phone ratio), roads (length of paved roads), and GDP growth significantly reduce poverty. Conversely, health facilities and electricity access showed no statistically meaningful effect. These findings underscore the necessity of prioritizing equitable education, digital connectivity, and inclusive economic policies to enhance poverty alleviation efforts. The study recommends targeted infrastructure investments in underserved regions, integration of digital literacy programs, and synergistic policies linking economic growth with social protection systems to ensure sustainable poverty reduction. This research contributes novel insights by integrating a comprehensive analysis of six infrastructure and economic variables across diverse provinces, highlighting stark regional disparities in development outcomes and proposing a synergistic policy framework that links digital infrastructure expansion with literacy programs to address accessibility gaps.